Modified copper alloy and preparation method thereof

By optimizing the Cr and Zr content and ratio in Cu-Cr-Zr alloys, combined with the microalloy regulation of C and N elements, a composite physical field coordinated regulation process is adopted to form the coupling distribution characteristics of nano-dispersed particles, precipitation phase and dislocation, which solves the problem that existing alloys are difficult to take into account high strength, high conductivity and high stress relaxation resistance, and achieves significant performance improvement.

CN119710355APending Publication Date: 2025-03-28CHINALCO RES INST OF SCI & TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411983407.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing Cu-Cr-Zr alloys to take into account both high strength, high conductivity and high stress relaxation resistance.

Method used

By optimizing the content and ratio of Cr and Zr elements, combined with the microalloy regulation of C and N elements, the coupling distribution characteristics of multi-size nano-difference particles, precipitation phase and dislocation are formed by the composite physics coordinated regulation of cast structure, double-stage high-temperature heat treatment, hot rolling, ultra-low temperature cycle deep cold rolling deformation, and pre-aging.

Benefits of technology

The strength, conductivity and stress relaxation resistance of modified copper alloy sheets have been significantly improved, meeting the demand for high-strength, high-conductivity and high-stress relaxation materials in the high-tech field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710355A_ABST
    Figure CN119710355A_ABST
Patent Text Reader

Abstract

The invention provides a modified copper alloy plate and a preparation method thereof. The modified copper alloy plate comprises the following components in percentage by weight: 0.8 to 1.5 percent of Cr element, 0.05 to 0.3 percent of Zr element, 0.001 to 0.10 percent of C element, 0.001 to 0.10 percent of N element and the balance of Cu element. According to the method, the precipitation behavior of the copper alloy is optimized by changing the content of the Cr element and the Zr element of the Cu-Cr-Zr alloy, and a large number of nano carbide and nitride dispersion particles are formed in a cast ingot matrix by fully utilizing the phase and distribution characteristics formed by solute elements such as C and N; by means of the method, dislocation uniform dispersion distribution can be effectively promoted, precipitation and distribution of a precipitation phase can be effectively regulated and controlled, and finally based on nano dispersion particles, precipitation phase and dislocation coupling distribution regulation and control, the alloy strength, the electric conductivity and the stress relaxation resistance can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper alloys, and in particular to a modified copper alloy and a preparation method thereof. Background Art

[0002] Due to its excellent mechanical and electrical properties, high-strength and high-conductivity copper alloys have been widely used in electrified contact wires, lead frames, resistance welding electrode materials, and continuous casting steel crystallizers. However, with the rapid development of these fields, higher requirements have been put forward for the comprehensive performance of high-strength and high-conductivity copper alloys. Taking the electrified railway contact wire as an example, the high-strength and high-conductivity copper alloy contact wire, as a key component, is an important condition for ensuring the safe and stable operation of the electrified railway. The electrified contact wire transmits the received electric energy to the locomotive by friction with the pantograph slide. When transmitting electric energy, the contact wire will not only be constantly worn, but also need to continuously withstand the tension of the wire and the influence of various forces such as additional force, which can easily cause the contact wire to fail. In severe cases, it will be disconnected, that is, the high-speed rail will be powered off, which will cause very bad subsequent effects. Therefore, the copper alloy raw materials used for the electrified contact wire not only need to have good electrical and thermal conductivity, but also the softening temperature, tensile strength, wear resistance and corrosion resistance of the alloy must be high enough. In addition, in recent years, with the rapid development of electronic information technology, especially the semiconductor industry with integrated circuits as the core as the pillar industry of modern information technology has developed by leaps and bounds, resulting in more and more stringent requirements for material varieties and performance. Since integrated circuits are mainly composed of chips and lead frames, the lead frame material plays the role of transmitting signals, protecting internal components and dissipating heat to the outside, and is a key component of integrated circuits. At present, more than 80% of the integrated circuit lead frame materials are made of high-precision copper alloys. There are more than 100 kinds of copper alloys developed for lead frames in the world, and the alloy systems mainly include Cu-Fe-P system, Cu-Ni-Si system and Cu-Cr system. With the rapid development of the electronic information industry, the huge number of leads of high-end integrated circuits has continuously reduced the width, distance and thickness between the leads, resulting in the continuous development of lead frames towards multi-pin, miniaturization, thinness, high precision and low cost, which requires the selected copper alloy plate to have high tensile strength, high conductivity, high thermal conductivity, and high requirements for the plasticity, ductility, heat resistance, weldability and stress relaxation resistance of the alloy. It is believed that the tensile strength of the copper alloy sheet used for the perfect integrated circuit frame material should be higher than 600MPa, the conductivity should be higher than 80%IACS, and the softening temperature of the alloy should not be lower than 500℃.

[0003] Compared with other solute elements, Cr and Zr have little effect on the conductivity of Cu alloy matrix. Cu-Cr and Cu-Zr binary alloys generally have great advantages in conductivity (generally above 80% IACS). However, in terms of strength, neither can achieve very high strength, and the maximum can only reach about 480MPa. Due to the limitation of strength, the application of these two alloys in society is relatively narrow. For this reason, a large number of studies on microalloying regulation have been conducted to address the insufficient performance of Cu-Cr and Cu-Zr binary alloys. Studies have found that adding Zr to Cu-Cr alloys can slow down the growth of Cr phase, accelerate the segregation of Cr particles during aging, and promote the precipitation rate during aging. The Cr phase precipitated in the alloy matrix can also be characterized by fine and dispersed distribution. The strength of the alloy can be greatly improved, and the addition of Zr has little effect on the conductivity of the alloy. In addition, some studies have found that after adding Zr elements, the Zr atoms dissolved in the matrix during aging can occupy some vacancy defects in the alloy matrix, which has a certain hindering effect on the diffusion of Cr atoms, resulting in an increase in the difficulty of coarsening the Cr precipitate phase and a relatively small size, which can ultimately improve the strength and high-temperature softening properties of the Cu-Cr-Zr alloy. Overall, the Cu-Cr-Zr alloy is one of the key copper alloys currently developed that can have both high strength and high conductivity. A large number of studies have shown that this series of alloy plates and strips generally need to be regulated by a deformation aging heat treatment process that combines solid solution, cold deformation and aging to have both high strength and high conductivity. Simple solid solution + aging cannot meet the high strength requirements, and the relevant mechanism is not yet clear. In addition, although the addition of Zr significantly promotes the aging precipitation of Cu-Cr alloys, the content of Cr and Zr and their matching ratio are not clear. With the change of the content of Cr and Zr and their matching ratio, the hot working process also needs to be properly optimized to significantly improve the comprehensive performance of the alloy. However, up to now, most alloy development focuses on the addition of trace amounts of Zr elements to carry out deformation heat treatment regulation research, which is not only unsystematic, but also difficult to find the optimal composition design principles and range under the condition that the interaction mechanism between Cr and Zr elements is not clear enough, and then through the appropriate process to significantly improve its comprehensive performance.

[0004] According to the performance requirements of the new generation of high-strength and high-conductivity copper alloy materials, and considering that the key factors affecting the strength, conductivity, high-temperature softening resistance, and stress relaxation resistance of the alloy are still composition and process. Therefore, it is very necessary to develop a preparation method that effectively promotes the strength, conductivity, and stress relaxation resistance of Cu-Cr-Zr alloys, so as to better meet the urgent needs of this type of material in the field of high-tech. In addition, this new Cu-Cr-Zr alloy material and its preparation process will also have an important inspiration and driving effect on the further development of other new metal materials. Summary of the invention

[0005] The main purpose of the present invention is to provide a modified copper alloy plate and a preparation method thereof, so as to solve the problem that it is difficult to simultaneously achieve high strength, high conductivity and high stress relaxation resistance in Cu-Cr-Zr alloys in the prior art.

[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a modified copper alloy plate is provided, which comprises, by mass percentage, 0.8-1.5wt% of Cr element, 0.05-0.3wt% of Zr element, 0.001-0.10wt% of C element, 0.001-0.10wt% of N element, and the rest is Cu element.

[0007] Furthermore, in terms of mass percentage, the modified copper alloy sheet material comprises: 0.8-1.4wt% of Cr element, 0.05-0.22wt% of Zr element, 0.001-0.10wt% of C element, 0.001-0.10wt% of N element, and the rest is Cu element; and / or the weight ratio of Cr element to Zr element is 5-13:1.

[0008] Furthermore, the modified copper alloy sheet includes nano-dispersed particles, and the nano-dispersed particles include nano-carbide dispersed particles and nano-nitride dispersed particles, wherein the mass content of the nano-carbide dispersed particles is 0.005-0.5wt%, preferably 0.015-0.048wt%, and / or the mass content of the nano-nitride dispersed particles is 0.0043-0.43wt%, preferably 0.013-0.042wt%; and / or the dislocation density of the modified copper alloy sheet is 1.1×10 15 ~2.0×10 15 m -2 , and / or the modified copper alloy plate also includes a precipitate phase, and the nano-dispersed particles and the precipitate phase are dispersedly distributed.

[0009] Furthermore, the tensile strength of the modified copper alloy sheet is 554.3-628.2 MPa, the yield strength of the modified copper alloy sheet is 525.6-626.1 MPa, the conductivity of the modified copper alloy sheet is 60.3-84.2% IACS, the room temperature and 1000h stress relaxation rate of the modified copper alloy sheet is 5.86-18.2%, and the hardness of the modified copper alloy sheet is 152.2-209.4 HV.

[0010] According to one aspect of the present invention, a preparation method of the modified copper alloy sheet is provided, and the preparation method comprises: step S1, preparing ingredients according to the contents of the Cr element, Zr element and Cu element, and sequentially melting, heat-insulating, physically stirring and temperature-controlled casting the ingredients to obtain a copper alloy ingot; step S2, sequentially performing a first high-temperature heat treatment, a first cooling treatment, a second high-temperature heat treatment, a second cooling treatment, hot rolling deformation and a third cooling treatment on the copper alloy ingot to obtain a hot-rolled copper alloy sheet; step S3, sequentially performing a first ultra-low temperature cycle deep cold rolling deformation and a first aging treatment on the hot-rolled copper alloy sheet to obtain a first-deformed copper alloy sheet; step S4, performing a second ultra-low temperature cycle deep cold rolling deformation on the first-deformed copper alloy sheet to obtain a modified copper alloy sheet; wherein, melting and heat-insulating are performed in a graphite crucible in a vacuum medium-frequency induction furnace, and stirring and casting are performed in a nitrogen atmosphere; the starting rolling temperature of the hot rolling deformation is 700-840°C, and the final rolling temperature of the hot rolling deformation is >500°C.

[0011] Further, the above step S1 includes: step S11, when the vacuum degree is less than 0.1 Pa, the ingredients are subjected to a first heating and a first heat preservation in a graphite crucible, and then heated and melted, and a second heat preservation is performed to obtain a copper alloy melt; step S12, the copper alloy melt is subjected to a first physical field stirring and a first cooling treatment in sequence, and then subjected to a second physical field stirring and a second cooling treatment in a nitrogen atmosphere, and then temperature-controlled casting; wherein the pressure of the nitrogen atmosphere is 10 4 ~10 5 Pa; and / or, the temperature of the first insulation is 300-400°C, and the time of the first insulation is 30-50min; and / or, the temperature of the second insulation is 1200-1300°C, and the temperature of the second insulation is 10-20min; and / or, the time of the first physical field stirring is 30s-90s, and the temperature of the copper alloy melt after the first cooling treatment is 1100-1200°C; and / or, the time of the second physical field stirring is 30s-90s, and the temperature of the copper alloy melt after the second cooling treatment is 1150-1250°C.

[0012] Further, in the above step S2, the temperature of the first high temperature heat treatment is 850-980°C, the heating rate of the first high temperature heat treatment is >100°C / min, and the time of the first high temperature heat treatment is 2-20h; and / or, the cooling rate of the first cooling treatment is >120°C / min; and / or, the temperature of the second high temperature heat treatment is 700-840°C, the heating rate of the second high temperature heat treatment is >100°C / min, and the time of the second high temperature heat treatment is 10-60min; and / or, the cooling rate of the second cooling treatment is >120°C / min; and / or, the deformation amount of hot rolling deformation is 70-80%, and the deformation amount of hot rolling deformation is 10-20%; and / or, the cooling rate of the third cooling treatment is >100°C / s.

[0013] Further, when the temperature of the above-mentioned first aging is 380-500°C and the time of the first aging is 7-15h, a modified copper alloy sheet is obtained through steps S3 and S4; wherein, the temperature of the first ultra-low temperature cycle deep cold rolling deformation is -100--190°C, and the deformation amount of the first ultra-low temperature cycle deep cold rolling deformation is 50-65%, and preferably the number of cycles of the first ultra-low temperature cycle deep cold rolling deformation is >15 times; the heating rate of the first aging is >50°C / min; and / or, the temperature of the second ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the second ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the second ultra-low temperature cycle deep cold rolling deformation is >15 times.

[0014] Furthermore, when the temperature of the first aging is 380-500°C and the time of the first aging is 0.2-3h, the preparation method also includes: step S5, subjecting the copper alloy sheet obtained after the second ultra-low temperature cycle deep cold rolling deformation to a second aging treatment, a third ultra-low temperature cycle deep cold rolling deformation, a third aging treatment and a fourth ultra-low temperature cycle deep cold rolling deformation in sequence to obtain a modified copper alloy sheet.

[0015] Further, in the above step S5, the temperature of the second aging is 380-480°C, the time of the second aging is 0.5-5h, and the heating rate of the second aging is >50°C / min; and / or, the temperature of the third ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the third ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the third ultra-low temperature cycle deep cold rolling deformation is >10 times; the temperature of the third aging is 350-460°C, the time of the third aging is 15-25h, and the heating rate of the third aging is >50°C / min; and / or, the temperature of the fourth ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the fourth ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the fourth ultra-low temperature cycle deep cold rolling deformation is >10 times.

[0016] By applying the technical scheme of the present invention, the present invention not only optimizes the precipitation behavior of the modified copper alloy sheet by changing the content of Cr and Zr elements in the Cu-Cr-Zr alloy, but also fully utilizes the characteristics that solute elements such as C and N can form carbides and nitrides with Cr and Zr, and fully controls the melting and casting process to form a large number of nano-carbide and nitride dispersed particles in the ingot matrix, thereby effectively affecting the dislocation slip and distribution, precipitation phase precipitation and its coupling distribution characteristics with dislocations in the subsequent processing of the alloy, and finally significantly improves the strength, conductivity and stress relaxation resistance of the modified copper alloy sheet based on the coupling distribution characteristics of nano-dispersed particles, precipitation phases and dislocations. The modified copper alloy sheet with high strength, high conductivity and high stress relaxation resistance developed by the present invention will not increase the production cost of the alloy, but also has excellent comprehensive performance, and at the same time, the plasticity and processing performance of the copper alloy are also improved to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0018] Figure 1 The following is a flow chart of the preparation process of the modified copper alloy of Example 1 of the present application;

[0019] Figure 2 The room temperature stress relaxation resistance curve corresponding to the modified copper alloy plate obtained in Example 1 of the present application is shown;

[0020] Figure 3 The room temperature stress relaxation resistance curve corresponding to the modified copper alloy plate obtained in Example 3 of the present application is shown;

[0021] Figure 4 The 150°C high temperature stress relaxation resistance curve of the modified copper alloy sheet obtained in Example 1 of the present application is shown;

[0022] Figure 5 The TEM structure characterization result diagram of the nano-dispersed particles, precipitate phase and dislocation coupling distribution of the modified copper alloy plate obtained in Example 1 of the present application is shown;

[0023] Figure 6 The HRTEM structure characterization result diagram of the modified copper alloy plate obtained in Example 1 of the present application is shown;

[0024] Figure 7 The HRTEM microstructure characterization result diagram of the modified copper alloy plate obtained in Example 1 of the present application after a 150° C. high temperature stress relaxation test is shown;

[0025] Figure 8The 150°C high temperature stress relaxation resistance curve corresponding to the modified copper alloy plate obtained in Example 5 of the present application is shown. DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0027] As analyzed in the background technology of this application, the prior art has the problem of being difficult to simultaneously take into account high strength, high conductivity and high stress relaxation resistance. In order to solve the above problems, this application provides a modified copper alloy plate and a preparation method thereof.

[0028] In a typical embodiment of the present application, a modified copper alloy sheet is provided. Measured by mass percentage, the modified copper alloy sheet comprises: 0.8-1.5wt% of Cr element, 0.05-0.3wt% of Zr element, 0.001-0.10wt% of C element, 0.001-0.10wt% of N element, and the rest is Cu element.

[0029] The present invention not only optimizes the precipitation behavior of the modified copper alloy sheet by changing the content of Cr and Zr elements in the Cu-Cr-Zr alloy, but also fully utilizes the characteristics that solute elements such as C and N can form corresponding carbides and nitrides with Cr and Zr, and can also form a large number of nano carbide and nitride dispersed particles in the ingot matrix by controlling the melting and casting process, thereby effectively affecting the dislocation slip and distribution, precipitation phase precipitation and its coupling distribution characteristics with dislocations in the subsequent processing of the alloy, and finally significantly improving the strength, electrical conductivity and stress relaxation resistance of the modified copper alloy sheet based on the coupling distribution characteristics of nano dispersed particles, precipitation phases and dislocations. The modified copper alloy sheet with high strength, high electrical conductivity and high stress relaxation resistance developed by the present invention will not increase the production cost of the alloy, but also has excellent comprehensive performance, and at the same time, the plasticity and processing performance of the copper alloy are also improved to a certain extent.

[0030] In order to further improve the synergistic effect of each element in the copper alloy, thereby improving the strength and electrical conductivity of the modified copper alloy, the modified copper alloy sheet includes, by mass percentage: 0.8-1.4wt% of Cr element, 0.05-0.22wt% of Zr element, 0.001-0.10wt% of C element, 0.001-0.10wt% of N element, and the rest is Cu element; and / or the weight ratio of Cr element to Zr element is 5-13:1. Among them, controlling the weight ratio of Cr element to Zr element within this range has a significant promoting effect on the aging precipitation of Cu-Cr-Zr alloy.

[0031] In one embodiment of the present application, the modified copper alloy sheet includes nano-dispersed particles, and the nano-dispersed particles include nano-carbide dispersed particles and nano-nitride dispersed particles, wherein the mass content of the nano-carbide dispersed particles is 0.005-0.5wt%, preferably 0.015-0.048wt%, and / or the mass content of the nano-nitride dispersed particles is 0.0043-0.43wt%, preferably 0.013-0.042wt%; and / or the dislocation density of the modified copper alloy sheet is 1.1×10 15 ~2.0×10 15 m -2 , and / or the modified copper alloy plate also includes a precipitate phase, and the nano-dispersed particles and the precipitate phase are dispersedly distributed.

[0032] Controlling the content of nano-carbide particles within the above range is beneficial to strengthening the precipitation effect and grain refinement, and is also beneficial to the low-temperature phase transformation, so that a higher dislocation density exists in the low-temperature phase transformation structure, thereby helping to improve the strength of the modified copper alloy sheet. Preferably controlling the content of nitride dispersed particles within the above range is beneficial to inhibiting the precipitation of carbides at the grain boundaries of the modified copper alloy sheet, and is also beneficial to reducing the degree of Cr depletion at the grain boundaries, thereby improving the strength of the modified copper alloy sheet. Preferably controlling the dislocation slip and dislocation coupling distribution range of the modified copper alloy sheet is beneficial to improving the mechanical properties and grain refinement of the modified copper alloy sheet, and is also beneficial to improving the yield strength and fracture strength of the modified copper alloy sheet, thereby helping to improve the comprehensive performance of the modified copper alloy sheet. Further, by controlling the content of the above nano-carbide dispersed particles and nitride dispersed particles, and optimizing the dislocation slip and dislocation coupling distribution of the modified copper alloy sheet, the above modified copper alloy sheet has excellent tensile strength, electrical conductivity, stress relaxation rate and hardness, thereby improving the overall performance of the copper alloy sheet.

[0033] In one embodiment of the present application, the tensile strength of the modified copper alloy sheet is 554.3-628.2 MPa, the yield strength of the modified copper alloy sheet is 525.6-626.1 MPa, the conductivity of the modified copper alloy sheet is 60.3-84.2% IACS, the room temperature and 1000h stress relaxation rate of the modified copper alloy sheet is 5.86-18.2%, and the hardness of the modified copper alloy sheet is 152.2-209.4 HV.

[0034] The modified copper alloy sheet with such tensile strength, conductivity and stress relaxation rate can better serve as a substitute material for the modified copper alloy sheet for traditional lead frames, and can well meet the urgent demand for high-strength, high-conductivity and high-stress relaxation resistance modified copper alloy sheet for manufacturing typical components in many high-tech fields such as the electronics industry, aerospace, instrumentation and household appliances.

[0035] In another typical embodiment of the present application, a preparation method of the modified copper alloy sheet is provided, and the preparation method comprises: step S1, preparing ingredients according to the contents of the above-mentioned Cr element, Zr element and Cu element, and sequentially melting, heat-insulating, physically stirring and temperature-controlled casting the ingredients to obtain a copper alloy ingot; step S2, sequentially performing a first high-temperature heat treatment, a first cooling treatment, a second high-temperature heat treatment, a second cooling treatment, hot rolling deformation and a third cooling treatment on the copper alloy ingot to obtain a hot-rolled copper alloy sheet; step S3, sequentially performing a first ultra-low temperature cycle deep cold rolling deformation and a first aging treatment on the hot-rolled copper alloy sheet to obtain a first-deformed copper alloy sheet; step S4, performing a second ultra-low temperature cycle deep cold rolling deformation on the first-deformed copper alloy sheet to obtain a modified copper alloy sheet; wherein, melting and heat-insulating are performed in a graphite crucible in a vacuum medium-frequency induction furnace, and stirring and casting are performed in a nitrogen atmosphere; the starting rolling temperature of the hot rolling deformation is 700-840°C, and the final rolling temperature of the hot rolling deformation is >500°C.

[0036] The present application coordinates the formation of nano-precipitate phase and its coupling distribution characteristics with dislocations through the coordinated regulation of cast structure, two-stage high-temperature heat treatment, hot rolling, ultra-low temperature cyclic deep cold rolling deformation and pre-aging processes by composite physical fields. Ultimately, based on the acquisition of multi-sized nano-dispersed particles, precipitate phase and dislocation coupling distribution characteristics, the strength, conductivity and stress relaxation resistance of the modified copper alloy are significantly improved, which are significantly higher than the corresponding performance of traditional Cu-Cr-Zr alloys. Specifically, the present invention not only optimizes the precipitation behavior of the copper alloy by changing the Cr, Zr content and Cr / Zr ratio of the Cu-Cr-Zr alloy, but also introduces the microalloying element C by making full use of the graphite crucible as a casting medium in the smelting process, and introduces the N element in the copper alloy by physical field stirring and casting in a nitrogen atmosphere, thereby synergistically regulating the diffusion of the C element and the N element into the copper alloy solution and the formation and distribution of their phases through the electromagnetic field and the temperature field, and then forming a large number of nano-carbide dispersed particles and nitride dispersed particles in the matrix of the modified copper alloy sheet, thereby effectively affecting the dislocation slip and distribution, precipitation phase precipitation and its coupling distribution characteristics with dislocations in the subsequent processing of the alloy, and finally significantly improving the strength, conductivity and stress relaxation resistance of the modified copper alloy sheet based on the nano-dispersed particles, precipitation phase and dislocation coupling distribution characteristics. In addition, more importantly, by controlling the starting rolling temperature and the final rolling temperature of the hot rolling deformation within the above range, the subsequent separate solid solution process of the alloy can be omitted, the process flow can be further shortened, and the production cost of the alloy sheet and strip can be reduced.

[0037] On the basis of composition design and casting process control, the present invention further introduces a two-stage heat treatment process (i.e., a first high-temperature heat treatment and a second high-temperature heat treatment) during hot rolling deformation to control the distribution of solute elements (C elements and N elements) and phases. The first high-temperature heat treatment can effectively promote the dissolution of solute elements and control the element distribution. Then, the second high-temperature heat treatment can not only precipitate a small amount of dispersed particles in the copper alloy ingot matrix, but also can be directly used for hot rolling deformation after the second high-temperature heat treatment. While shortening the process flow, the key formed nano-dispersed particles can still effectively pin dislocations, thereby increasing the uniformity of dislocation distribution in the copper alloy ingot matrix. The present invention further introduces an ultra-low temperature cycle deep cold rolling deformation treatment after hot rolling deformation, further increasing the dislocation number density and the degree of uniform dislocation distribution in the copper alloy ingot matrix. In addition, since the fine particles uniformly dispersed in the copper alloy ingot matrix can effectively pin dislocations, the introduction of ultra-low temperature cyclic deep cold rolling deformation can not only rapidly multiply a large number of dislocations in the copper alloy ingot matrix, but also make the multiplied dislocations in the copper alloy ingot matrix present better uniform dispersion distribution characteristics, and the uniform distribution of the nano-precipitate phase induced by it during subsequent aging precipitation is increased. In order to effectively regulate the coupling distribution characteristics after the nano-precipitate phase and the dislocation, the present invention further introduces pre-aging after the first ultra-low temperature cyclic deep cold rolling deformation, so that a large number of nano-dispersed precipitation phases can be precipitated in the copper alloy ingot matrix. Subsequently, through this repeated deep cold rolling deformation and aging process coordinated regulation, not only can the dislocation distribution be further optimized, but also nano-dispersed particles of various sizes can be further induced to precipitate. In the repeated regulation process, the uniformity of dislocations and nano-dispersed particles of various sizes is significantly increased, and the coupling degree between the two is also better. Finally, based on the acquisition of suitable coupling distribution characteristics between various-sized nano-dispersed particles and dislocations, the strength, electrical conductivity and stress relaxation resistance of the developed modified copper alloy can be significantly improved. The modified copper alloy developed by the present invention can well meet the urgent needs of high-strength, high-conductivity and high-stress relaxation resistance copper alloys for manufacturing typical components in many high-tech fields such as the electronics industry, aerospace, instrumentation and household appliances. Therefore, this invention preparation method is not only very suitable for application in many high-tech fields, especially in fields with special requirements for high-strength and high-conductivity new copper alloys, but also especially for problems that often occur during the application of lead frame materials, such as poor stress relaxation resistance, etc., which can be well solved. In addition, this preparation technology also has certain guiding significance for the further development, processing and application of high-strength, high-conductivity copper alloys and other similar metal materials in other fields.

[0038] In one embodiment of the present application, the above-mentioned step S1 includes: step S11, when the vacuum degree is less than 0.1 Pa, the ingredients are subjected to a first heating and a first heat preservation in a graphite crucible, and then heated and melted and a second heat preservation are performed to obtain a copper alloy melt; step S12, the copper alloy melt is subjected to a first physical field stirring and a first cooling treatment in sequence, and then subjected to a second physical field stirring and a second cooling treatment in a nitrogen atmosphere, and then temperature-controlled casting; wherein the pressure of the nitrogen atmosphere is 10 4 ~10 5 Pa; and / or, the temperature of the first insulation is 300-400°C, and the time of the first insulation is 30-50min; and / or, the temperature of the second insulation is 1200-1300°C, and the temperature of the second insulation is 10-20min; and / or, the time of the first physical field stirring is 30s-90s, and the temperature of the copper alloy melt after the first cooling treatment is 1100-1200°C; and / or, the time of the second physical field stirring is 30s-90s, and the temperature of the copper alloy melt after the second cooling treatment is 1150-1250°C.

[0039] By controlling the range of the above conditions, it is beneficial to introduce solute elements such as micro-alloying elements C (graphite crucible) and N (filled with nitrogen) into the smelting process and the casting medium, and the diffusion of C and N elements into the solution can be regulated by the electromagnetic field and the temperature field in a coordinated manner, thereby forming a large number of nano-carbide and nitride dispersed particles in the ingot matrix, which can effectively affect the dislocation slip and distribution in the subsequent processing of the copper alloy, the precipitation phase precipitation and its coupling distribution characteristics with dislocations, and finally significantly improve the alloy strength, conductivity and stress relaxation resistance based on the coupling distribution characteristics of nano-dispersed particles and dislocations.

[0040] In one embodiment of the present application, in the above-mentioned step S2, the temperature of the first high-temperature heat treatment is 850-980°C, the heating rate of the first high-temperature heat treatment is >100°C / min, and the time of the first high-temperature heat treatment is 2-20h; and / or, the cooling rate of the first cooling treatment is >120°C / min; and / or, the temperature of the second high-temperature heat treatment is 700-840°C, the heating rate of the second high-temperature heat treatment is >100°C / min, and the time of the second high-temperature heat treatment is 10-60min; and / or, the cooling rate of the second cooling treatment is >120°C / min; and / or, the deformation amount of hot rolling deformation is 70-80%, and the deformation amount of each pass of hot rolling deformation is 10-20%; and / or, the cooling rate of the third cooling treatment is >100°C / s.

[0041] It is preferred to control the conditions of the first high temperature heat treatment within the above range, which is more conducive to promoting the dissolution of solute elements such as C and N elements and regulating the element distribution. By controlling the conditions of the second high temperature heat treatment within the above range, it is not only more conducive to precipitating a small amount of dispersed particles in the matrix, but also the temperature of the second high temperature heat treatment is reasonably selected and can be directly used for hot rolling deformation, shortening the process flow. More importantly, the formed nano dispersed particles can also effectively pin dislocations, thereby increasing the uniformity of dislocation distribution in the copper alloy matrix.

[0042] In one embodiment of the present application, when the temperature of the above-mentioned first aging is 380-500°C and the time of the first aging is 7-15h, a modified copper alloy sheet is obtained through steps S3 and S4; wherein, the temperature of the first ultra-low temperature cycle deep cold rolling deformation is -100--190°C, and the deformation amount of the first ultra-low temperature cycle deep cold rolling deformation is 50-65%, and preferably the number of cycles of the first ultra-low temperature cycle deep cold rolling deformation is >15 times; the heating rate of the first aging is >50°C / min; and / or, the temperature of the second ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the second ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the second ultra-low temperature cycle deep cold rolling deformation is >15 times.

[0043] After the hot rolling deformation process is regulated, although the dispersed particles formed can pin dislocations, the number of dislocations that can be generated by hot rolling is limited. In order to increase the dislocation number density and the degree of uniform distribution of dislocations, the present application further introduces a first ultra-low temperature cycle deep cold rolling deformation process after hot rolling deformation; by controlling the conditions of the first ultra-low temperature cycle deep cold rolling deformation within the above range, not only a large number of dislocations can be rapidly multiplied in the alloy matrix, but also the multiplied dislocations in the alloy matrix can be made to have better uniform dispersion distribution characteristics, which is beneficial to improving the tensile strength, electrical conductivity and stress relaxation resistance of the copper alloy. In order to effectively regulate the coupling distribution characteristics of the nano-precipitation phase and the dislocation, the present invention further introduces the first aging after the ultra-low temperature cycle deep cold rolling deformation, and by controlling the time and heating rate of the first aging, more nano-dispersed precipitation phases can be precipitated in the copper alloy matrix.

[0044] In one embodiment of the present application, when the temperature of the above-mentioned first aging is 380-500°C and the time of the first aging is 0.2-3h, the preparation method also includes: step S5, the copper alloy sheet obtained after the second ultra-low temperature cycle deep cold rolling deformation is subjected to a second aging treatment, a third ultra-low temperature cycle deep cold rolling deformation, a third aging treatment and a fourth ultra-low temperature cycle deep cold rolling deformation in sequence to obtain a modified copper alloy sheet.

[0045] In the process of repeated ultra-low temperature cycle deep cold rolling deformation control, the uniformity of dislocations and nano-dispersed particles of various sizes is significantly increased, and the coupling degree between the two is also better. Therefore, when the first aging time is short, the second ultra-low temperature cycle deep cold rolling deformation, the second aging, the third ultra-low temperature cycle deep cold rolling deformation, the third aging and the fourth ultra-low temperature cycle deep cold rolling deformation are sequentially performed after the first ultra-low temperature cycle deep cold rolling deformation and the first aging treatment in the present application. The specific conditions are preferably as follows:

[0046] In step S5, the temperature of the second aging is 380-480°C, the time of the second aging is 0.5-5h, and the heating rate of the second aging is >50°C / min; and / or, the temperature of the third ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the third ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the third ultra-low temperature cycle deep cold rolling deformation is >10 times; the temperature of the third aging is 350-460°C, the time of the third aging is 15-25h, and the heating rate of the third aging is >50°C / min; and / or, the temperature of the fourth ultra-low temperature cycle deep cold rolling deformation is -100--190°C, the deformation amount of the fourth ultra-low temperature cycle deep cold rolling deformation is 40-65%, and the number of cycles of the fourth ultra-low temperature cycle deep cold rolling deformation is >10 times.

[0047] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0048] according to Figure 1 The preparation process flow chart of the modified copper alloy shown in the figure is as follows: batching, melting, heat preservation, physical field stirring and temperature-controlled casting in sequence → first high-temperature heat treatment, first cooling treatment, second high-temperature heat treatment, second cooling treatment → hot rolling deformation, third cooling treatment → first ultra-low temperature cycle deep cold rolling deformation and first aging treatment → second ultra-low temperature cycle deep cold rolling deformation. After the above multi-process thermal processing regulation, the nano-dispersed particles, precipitation phase and dislocation coupling distribution characteristics can be controlled, and finally the developed copper alloy has high strength, high conductivity and high stress relaxation resistance. The chemical composition of the alloy in the specific embodiment is as follows:

[0049]

[0050]

[0051] Example 1

[0052] The ingredients are prepared according to the alloy number 1# (except C and N elements). The raw materials used for melting and casting are 99.9wt% electrolytic high-purity Cu, Cu-10wt% Cr, and Cu-20wt% Zr intermediate alloys. First, prepare the alloy, place the above raw materials in a high-purity graphite crucible of a vacuum medium-frequency induction melting furnace, and when the vacuum degree is 0.08Pa, start heating, slowly heat to 300-400℃ and keep warm for 30min, then directly and quickly heat until all the copper alloy ingredients are melted. When the temperature rises to 1200-1300℃, keep warm for 10-20min, and then stir the melt with a 70-kilowatt high-power electromagnetic stirrer for 35s. Then, when the melt temperature drops to 1200℃, fill it with nitrogen to make the pressure reach 10 4 After the temperature reaches 0.04 Pa, the solution is stirred with a 70-kW high-power electromagnetic stirrer for 35 seconds. Then, when the solution temperature drops and stabilizes at 1250°C, casting is started. The casting speed is controlled to avoid shrinkage cavities as much as possible. At the same time, the solution solidification rate is controlled to be >50°C / s. After the solution is completely solidified, the vacuum is broken and the copper alloy ingot is taken out.

[0053] The copper alloy ingot is subjected to a first high-temperature heat treatment, the heating rate is controlled to be greater than 100°C / min, and when the temperature rises to 870°C, it is kept warm, and after keeping warm for 16 hours, a first cooling treatment is performed, and the cooling rate of the first cooling treatment is greater than 120°C / min. When the temperature drops to 780°C, cooling is stopped, and then a second high-temperature heat treatment is performed. After keeping warm for 20 minutes, it is directly subjected to hot rolling deformation treatment, and the final rolling temperature is greater than 500°C for unidirectional rolling, and the total deformation is controlled to be 70-80%, and the deformation per pass is 10-20%. After the last hot rolling, rapid cooling is performed, and the cooling rate is greater than 100°C / s, to obtain a copper alloy plate after hot rolling deformation;

[0054] The copper alloy plate after hot rolling deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 14% and a deformation amount of 3 to 10% per pass. Then, the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 10% and a deformation amount of 3 to 10% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, so that the total deformation of the copper alloy plate finally reaches 55%; then, the temperature is increased, and the heating rate is greater than 50°C / min. When the temperature rises to 390°C, the first aging treatment is performed, and the temperature is kept for 0.6h, and then cooled in air to obtain the copper alloy plate after the first deformation;

[0055] The copper alloy sheet after the first deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100--190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 12% and a deformation amount of 3-10% per pass, and then the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 8 minutes, and when the temperature drops to -100--190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 8% and a deformation amount of 3-10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, and finally the total deformation amount of the copper alloy sheet reaches 55%; then the temperature is increased, and the heating rate is 60°C / min, and when the temperature rises to 400°C, a second aging treatment is performed, and the temperature is kept for 2 hours, and then cooled in air to obtain the copper alloy sheet after the second deformation;

[0056] The copper alloy plate after the second deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 10% and a deformation amount of 3-10% per pass, and then the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 3 to 10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation amount of the copper alloy plate finally reaches 55%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 390°C, a third aging treatment is performed, and the temperature is kept for 22 hours, and then cooled in air to obtain the copper alloy plate after the third deformation;

[0057] The copper alloy plate after the third deformation is placed in a liquid nitrogen tank for 20 minutes. When the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 1-5% per pass. Then, the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes. When the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 5% and a deformation amount of 1-7% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation of the copper alloy plate reaches 55%, and the above modified copper alloy is finally obtained. The corresponding room temperature stress relaxation resistance curve is shown in FIG. Figure 2 The corresponding 150℃ high temperature stress relaxation curve is shown in Figure 4 As shown in the figure, the TEM structure characterization results of the nano-dispersed particles, precipitate phase and dislocation coupling distribution of the modified copper alloy sheet are shown in Figure 5 As shown in the figure, the HRTEM microstructure characterization results of the modified copper alloy sheet are shown in Figure 6 The HRTEM microstructure characterization results after the 150°C high temperature stress relaxation test are shown in Figure 7 The corresponding mechanical properties and 150℃ stress relaxation resistance results are shown in Tables 2, 3 and 4

[0058] Example 2

[0059] The ingredients are prepared according to the alloy number 2# (except C and N elements). The raw materials used for melting and casting are 99.9wt% electrolytic high-purity Cu, Cu-10wt% Cr, and Cu-20wt% Zr intermediate alloys. First, prepare the alloy, place the above raw materials in a high-purity graphite crucible of a vacuum medium-frequency induction melting furnace, and when the vacuum degree is 0.05Pa, start heating, slowly heat to 300-400℃ and keep warm for 30min, then directly and quickly heat until all the copper alloy ingredients are melted. When the temperature rises to 1200-1300℃, keep warm for 10-20min, and then stir the melt with a 70-kilowatt high-power electromagnetic stirrer for 50s. Then, when the melt temperature drops to 1200℃, fill it with nitrogen to make the pressure reach 10 4 After the temperature reaches 0.0400 Pa, the solution is stirred with a 70-kW high-power electromagnetic stirrer for 50 seconds. Then, when the solution temperature drops and stabilizes at 1250°C, casting is started. The casting speed is controlled to avoid shrinkage cavities as much as possible. At the same time, the solution solidification rate is controlled to be >50°C / s. After the solution is completely solidified, the vacuum is broken and the copper alloy ingot is taken out.

[0060] The copper alloy ingot is subjected to a first high-temperature heat treatment, the heating rate is controlled to be greater than 100°C / min, and when the temperature rises to 900°C, it is kept warm, and after keeping warm for 17 hours, a first cooling treatment is performed, and the cooling rate of the first cooling treatment is greater than 120°C / min. When the temperature drops to 800°C, cooling is stopped, and then a second high-temperature heat treatment is performed. After keeping warm for 30 minutes, it is directly subjected to hot rolling deformation treatment, the final rolling temperature is greater than 500°C, and unidirectional rolling is performed, the total deformation is controlled to be 70-80%, and the deformation per pass is 10-20%. After the last hot rolling, rapid cooling is performed, and the cooling rate is greater than 100°C / s, to obtain a copper alloy plate after hot rolling deformation;

[0061] The copper alloy plate after hot rolling deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 14% and a deformation amount of 3-10% per pass. Then, the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 10% and a deformation amount of 3-10% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, so that the total deformation of the copper alloy plate finally reaches 65%; then, the temperature is increased, and the heating rate is greater than 50°C / min. When the temperature rises to 410°C, the first aging treatment is performed, and the temperature is kept for 1 hour, and then cooled in air to obtain the copper alloy plate after the first deformation;

[0062] The copper alloy sheet after the first deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 12% and a deformation amount of 3-10% per pass, and then the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 8% and a deformation amount of 3-10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, and finally the total deformation amount of the copper alloy sheet reaches 55%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 420°C, a second aging treatment is performed, and the temperature is kept for 2.5 hours, and then cooled in air to obtain the copper alloy sheet after the second deformation;

[0063] The copper alloy cast plate after the second deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 10% and a deformation amount of 3-10% per pass, and then the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 3-10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation amount of the copper alloy plate finally reaches 65%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 420°C, a third aging treatment is performed, and the temperature is kept for 23 hours, and then cooled in air to obtain a copper alloy plate after the third deformation;

[0064] The copper alloy sheet after the third deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 7% and a deformation amount of 1-5% per pass. Then, the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 5% and a deformation amount of 1-7% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation of the copper alloy sheet reaches 40%, and the above modified copper alloy is finally obtained. The corresponding mechanical properties and 150°C stress relaxation resistance results are shown in Tables 2, 3 and 4.

[0065] Example 3

[0066] The ingredients are prepared according to the 3# alloy number (except C and N elements). The raw materials used for melting and casting are 99.9wt% electrolytic high-purity Cu, Cu-10wt% Cr, and Cu-20wt% Zr intermediate alloys. First, prepare the alloy, place the above raw materials in a high-purity graphite crucible of a vacuum medium-frequency induction melting furnace, and when the vacuum degree is 0.05Pa, start heating, slowly heat to 300-400℃ and keep warm for 30min, then directly and quickly heat until all the copper alloy ingredients are melted. When the temperature rises to 1200-1300℃, keep warm for 10-20min, and then stir the melt with a 70-kilowatt high-power electromagnetic stirrer for 70s. Then, when the melt temperature drops to 1200℃, fill it with nitrogen to make the pressure reach 10 5 After the temperature reaches 0.04 Pa, the solution is stirred with a 70-kW high-power electromagnetic stirrer for 70 seconds. Then, when the solution temperature drops and stabilizes at 1250°C, casting is started. The casting speed is controlled to avoid shrinkage cavities as much as possible. At the same time, the solution solidification rate is controlled to be >50°C / s. After the solution is completely solidified, the vacuum is broken and the copper alloy ingot is taken out.

[0067] The copper alloy ingot is subjected to a first high-temperature heat treatment, the heating rate is controlled to be greater than 100°C / min, and when the temperature rises to 920°C, it is kept warm, and after keeping warm for 18 hours, a first cooling treatment is performed, and the cooling rate of the first cooling treatment is greater than 120°C / min. When the temperature drops to 820°C, cooling is stopped, and then a second high-temperature heat treatment is performed. After keeping warm for 40 minutes, it is directly subjected to hot rolling deformation treatment, and the final rolling temperature is greater than 500°C for unidirectional rolling, and the total deformation is controlled to be 70-80%, and the deformation per pass is 10-20%. After the last hot rolling, rapid cooling is performed, and the cooling rate is greater than 100°C / s, to obtain a copper alloy plate after hot rolling deformation;

[0068] The copper alloy plate after hot rolling deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 14% and a deformation amount of 3-10% per pass. Then, the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 10% and a deformation amount of 3-10% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, so that the total deformation of the copper alloy plate finally reaches 65%; then, the temperature is increased, and the heating rate is greater than 50°C / min. When the temperature rises to 430°C, a first aging treatment is performed, and the temperature is kept for 2 hours, and then cooled in air to obtain a copper alloy plate after the first deformation;

[0069] The copper alloy sheet after the first deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 12% and a deformation amount of 3 to 10% per pass, and then the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 8% and a deformation amount of 3 to 10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, so that the total deformation amount of the copper alloy sheet finally reaches 65%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 440°C, a second aging treatment is performed, and the temperature is kept for 3.5 hours, and then cooled in air to obtain the copper alloy sheet after the second deformation;

[0070] The copper alloy sheet after the second deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 10% and a deformation amount of 3 to 10% per pass, and then the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 3 to 10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation amount of the copper alloy sheet finally reaches 40%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 440°C, a third aging treatment is performed, and the temperature is kept for 24 hours, and then cooled in air to obtain the copper alloy sheet after the third deformation;

[0071] The copper alloy sheet after the third deformation is placed in a liquid nitrogen tank for 20 minutes. When the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 1 to 5% per pass. Then, the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes. When the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 5% and a deformation amount of 1 to 7% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation of the copper alloy sheet reaches 40%, and the above modified copper alloy is finally obtained. The corresponding room temperature stress relaxation resistance curve is shown in FIG. Figure 3 The corresponding mechanical properties and stress relaxation resistance results at 150°C are shown in Tables 2, 3 and 4.

[0072] Example 4

[0073] The ingredients are prepared according to the 4# alloy number (except C and N elements). The raw materials used for melting and casting are 99.9wt% electrolytic high-purity Cu, Cu-10wt% Cr, and Cu-20wt% Zr intermediate alloys. First, prepare the alloy, place the above raw materials in a high-purity graphite crucible of a vacuum medium-frequency induction melting furnace, and when the vacuum degree is 0.08Pa, start heating, slowly heat to 300-400℃ and keep warm for 30min, then directly and quickly heat until all the copper alloy ingredients are melted. When the temperature rises to 1200-1300℃, keep warm for 10-20min, and then stir the melt with a 70-kilowatt high-power electromagnetic stirrer for 90s. Then, when the melt temperature drops to 1200℃, fill it with nitrogen to make the pressure reach 10 6 After the temperature reaches 0.04 Pa, the solution is stirred with a 70-kW high-power electromagnetic stirrer for 90 seconds. Then, when the solution temperature drops and stabilizes at 1250°C, casting is started. The casting speed is controlled to avoid shrinkage cavities as much as possible. At the same time, the solution solidification rate is controlled to be >50°C / s. After the solution is completely solidified, the vacuum is broken and the copper alloy ingot is taken out.

[0074] The copper alloy ingot is subjected to a first high-temperature heat treatment, the heating rate is controlled to be greater than 100°C / min, and when the temperature rises to 940°C, it is kept warm, and after keeping warm for 19 hours, a first cooling treatment is performed, and the cooling rate of the first cooling treatment is greater than 120°C / min. When the temperature drops to 840°C, cooling is stopped, and then a second high-temperature heat treatment is performed. After keeping warm for 50 minutes, it is directly subjected to hot rolling deformation treatment, and the final rolling temperature is greater than 500°C for unidirectional rolling, and the total deformation is controlled to be 70-80%, and the deformation per pass is 10-20%. After the last hot rolling, rapid cooling is performed, and the cooling rate is greater than 100°C / s, to obtain a copper alloy plate after hot rolling deformation;

[0075] The copper alloy plate after hot rolling deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 14% and a deformation amount of 3 to 10% per pass. Then, the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 10% and a deformation amount of 3 to 10% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, so that the total deformation of the copper alloy plate finally reaches 65%; then, the temperature is increased, and the heating rate is greater than 50°C / min. When the temperature rises to 460°C, the first aging treatment is performed, and the temperature is kept for 4 hours, and then cooled in air to obtain the copper alloy plate after the first deformation;

[0076] The copper alloy sheet after the first deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 12% and a deformation amount of 3 to 10% per pass, and then the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 8% and a deformation amount of 3 to 10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 15 times, and finally the total deformation amount of the copper alloy sheet reaches 65%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 460°C, a second aging treatment is performed, and the temperature is kept for 5 hours, and then cooled in air to obtain the copper alloy sheet after the second deformation;

[0077] The copper alloy plate after the second deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 10% and a deformation amount of 3 to 10% per pass, and then the ultra-low temperature rolled copper alloy plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is subjected to synchronous rolling deformation, with a deformation amount of 7% and a deformation amount of 3 to 10% per pass, and the above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation of the copper alloy plate finally reaches 40%; then the temperature is increased, and the heating rate is greater than 50°C / min, and when the temperature rises to 460°C, a third aging treatment is performed, and the temperature is kept for 25 hours, and then cooled in air to obtain the copper alloy plate after the third deformation;

[0078] The copper alloy sheet after the third deformation is placed in a liquid nitrogen tank for 20 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 7% and a deformation amount of 1 to 5% per pass. Then, the ultra-low temperature rolled copper alloy sheet is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, and when the temperature drops to -100 to -190°C, it is synchronously rolled and deformed, with a deformation amount of 5% and a deformation amount of 1 to 7% per pass. The above process is repeated, and the number of low temperature deformation cycles is greater than 10 times, so that the total deformation of the copper alloy sheet reaches 65%, and the above copper modified alloy is finally obtained. The corresponding mechanical properties and 150°C stress relaxation resistance results are shown in Tables 2, 3 and 4.

[0079] Example 5

[0080] The difference from Example 1 is that, in the first aging, the temperature is 400°C, the time is 11h, the heating rate is greater than 50°C / min, and the temperature is air-cooled; the ultra-low temperature cycle deep cold rolling deformation, the number of low temperature deformation cycles is greater than 15 times, first placed in a liquid nitrogen tank for more than 20min, and then ultra-low temperature deformation is performed, the deformation temperature is -100 to -190°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; then the ultra-low temperature rolled plate is placed in a liquid nitrogen tank and cooled for 2 to 10min, the deformation temperature is -100 to -190°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; repeat the above process, and finally the total deformation amount of the alloy plate reaches 65%, and finally the above-mentioned modified copper alloy is obtained, and its 150°C high temperature stress relaxation resistance curve is as shown in Figure 8 The corresponding mechanical properties and 150℃ stress relaxation resistance results are shown in Tables 3 and 4.

[0081] Example 6

[0082] The difference from Example 2 is that, for the first aging, the temperature is 420°C, the time is 12h, the heating rate is greater than 50°C / min, and the process is air-cooled; the ultra-low temperature cyclic deep cold rolling deformation, the number of low temperature deformation cycles is greater than 15 times, first placed in a liquid nitrogen tank for more than 20 minutes, and then ultra-low temperature deformation is performed, the deformation temperature is -100 to -190°C, the deformation amount is 5%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; then the ultra-low temperature rolled plate is placed in a liquid nitrogen tank and cooled for 2 to 10 minutes, the deformation temperature is -100 to -190°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; the above process is repeated, and finally the total deformation amount of the alloy plate reaches 65%, and finally the above-mentioned modified copper alloy is obtained. The corresponding mechanical properties and stress relaxation resistance results at 150°C are shown in Tables 3 and 4

[0083] Example 7

[0084] The difference from Example 3 is that the pre-aging temperature is 440°C, the time is 13h, the heating rate is greater than 50°C / min, and the cooling is performed in air; (5) ultra-low temperature cycle deep cold rolling deformation, the number of low temperature deformation cycles is greater than 15 times, first placed in a liquid nitrogen tank for more than 20 minutes, and then ultra-low temperature deformation is performed, the deformation temperature is -100 to -1960°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; then the ultra-low temperature rolled plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, the deformation temperature is -100 to -190°C, the deformation amount is 5%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; repeat the above process, and finally the total deformation amount of the alloy plate reaches 40%, and finally the above copper alloy is obtained. The corresponding mechanical properties and 150°C stress relaxation resistance results are shown in Tables 3 and 4.

[0085] Example 8

[0086] The difference from Example 4 is that the pre-aging temperature is 460°C, the time is 15h, the heating rate is greater than 50°C / min, and the cooling is performed in air; (5) ultra-low temperature cycle deep cold rolling deformation, the number of low temperature deformation cycles is greater than 15 times, first placed in a liquid nitrogen tank for more than 20 minutes, and then ultra-low temperature deformation is performed, the deformation temperature is -100 to -190°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; then the ultra-low temperature rolled plate is placed in a liquid nitrogen tank for cooling for 2 to 10 minutes, the deformation temperature is -100 to -190°C, the deformation amount is 15%, the deformation method is synchronous rolling, and the deformation amount per pass is 3 to 10%; repeat the above process, and finally the total deformation amount of the alloy plate reaches 65%, and finally the above modified copper alloy is obtained. The corresponding mechanical properties and 150°C stress relaxation resistance results are shown in Tables 3 and 4.

[0087] Comparative Example 1

[0088] The difference from Example 1 is that the starting rolling temperature of hot rolling deformation is 850°C, the final rolling temperature of hot rolling deformation is 400°C, and solid solution treatment is required after hot rolling deformation. The conditions of solid solution treatment are 950°C and the time is 5h. The cooling method adopts water-cooled quenching treatment, and finally the above-mentioned modified copper alloy sheet is obtained. The corresponding mechanical properties of the modified copper alloy sheet are shown in Table 3, and the high temperature stress relaxation resistance at 150°C is shown in Table 4.

[0089] Performance Testing:

[0090] The mass content, dislocation density, and dislocation coupling distribution of the nano-carbide dispersed particles and nano-nitride dispersed particles in the modified copper alloy plates in the above embodiments and comparative examples were tested, and the test results are listed in Table 1.

[0091] Test method for the mass content of nano-carbide dispersed particles and nano-nitride dispersed particles in modified copper alloy plates: based on theoretical calculation and TEM organizational structure characterization method.

[0092] Testing method for dislocation density: The dislocation density in the alloy matrix was measured using the XRD method on an Empyrean diffractometer.

[0093] The testing method of dislocation coupling distribution is carried out by using TEM structure characterization on a JEM-F200 transmission electron microscope.

[0094] Table 1

[0095]

[0096] The hardness, electrical conductivity, tensile strength, yield strength and stress relaxation resistance of the modified copper alloys in the embodiments and comparative examples were measured, wherein the hardness, electrical conductivity, tensile strength and yield strength of the corresponding copper alloys after the third aging in Examples 1 to 4 are shown in Table 2; the hardness, electrical conductivity, tensile strength and yield strength of the modified copper alloy plates in all embodiments and comparative examples are shown in Table 3; the room temperature and high temperature stress relaxation resistance of the modified copper alloys in different embodiments and comparative examples are shown in Table 4.

[0097] Hardness test method of modified copper alloy: Test on EAM-3A-500 microhardness tester, and take the average value of 10 values ​​each time.

[0098] Conductivity test method of modified copper alloy: Use SIGMATEST 2.070 eddy current conductivity meter to test, and take the average value of 10 values ​​each time.

[0099] The tensile strength and yield strength test method of the modified copper alloy is carried out on an AG-Xplus tensile machine according to the international standard E8 / E8M-16a.

[0100] Test method for stress relaxation resistance of modified copper alloy: carried out according to international standard E328-21.

[0101] Table 2

[0102]

[0103]

[0104] Table 3

[0105]

[0106] Table 4

[0107]

[0108]

[0109] According to the above design ideas, the strength and electrical conductivity of the alloys prepared by Examples 1-4 do have large differences. It can be seen from Table 2 that with the changes in the Cr, Zr content and their ratios, as well as the changes in the hot working process, the strength of the series of alloys varies greatly. The 1# alloy developed in Example 1 has the highest strength after three-level aging regulation, reaching 534.9MPa, and the conductivity is 69.5%IACS. In comparison, the strength of the 2#, 3# and 4# alloys developed in Examples 2-4 is generally around 500MPa, but its conductivity is close to 90%IACS. If this state series of alloys is further regulated by ultra-low temperature cyclic deep cold rolling deformation, it can be seen from Table 1 that after the three-level aging regulation, due to the precipitation of a large number of nano-dispersed precipitation phases in the matrix, the alloy can induce a large number of uniformly dispersed dislocations to appear in the matrix after ultra-low temperature cyclic deep cold rolling deformation. At this time, it can be seen from Table 3 that although the conductivity of the alloy has been slightly reduced, the strength of the series of alloys has been greatly improved. The 1# alloy is as high as 628.2MPa, and the corresponding conductivity is also 63.5%IACS. The strength of the 2#, 3# and 4# alloys has also been greatly improved, among which the tensile strength of the 3# alloy is basically close to 600MPa, and the conductivity is still as high as 84.2%IACS. It can be seen that the key to improving the strength and conductivity of the series of alloys lies in the matching of Cr and Zr content, micro-alloying regulation, and the regulation of the precipitation of nano-dispersed precipitates and their coupling distribution with dislocations. Only when these influencing factors can be well optimized and controlled, the strength and conductivity of the developed alloys can be significantly improved. If the typical alloys regulated by Examples 1-4, such as 1# and 3# alloys, are further evaluated for their stress relaxation resistance at room temperature or 1-4# alloys at high temperature, it can be found, as shown in Table 4, Figure 2 and Figure 3 As shown in the table and figure, it can be seen that the relaxation rate of the 1# alloy developed in Example 1 after 6.5 hours of room temperature stress relaxation in the final state is only 3.715%, while the relaxation rate of the 3# alloy developed in Example 3 after 24 hours of room temperature stress relaxation in the final state is 11.396%. Considering that the long-term stress relaxation rate can be obtained by fitting regression based on the short-time relaxation rate, the 1000h room temperature stress relaxation rate of the typical alloy can be fitted and evaluated based on the short-time stress relaxation. Assuming that the movable density of the copper alloy gradually decreases with time during the stress relaxation process, the kinetic regression equation of the alloy during the stress relaxation process is as follows, σ*=[aln(tb)+c] d , where σ* is the residual stress, and a, b, c and d are all constants related to the structure at the experimental temperature. Based on the residual stress of the invention alloy under short-time loading time, the regression equations of 1# and 3# alloys at room temperature are calculated as follows: 1# alloy: [1.54*10 -5 ln(t+0.013)+2.07*10 -3] -0.92 , 3# alloy: [1.19*10 -5 ln(t-0.05)+7.93*10 -4 ] -0.78 . Then, according to the established regression equation, the time t=1000h is substituted into the equation, and the residual stress and stress relaxation rate of the 1# and 3# alloys regulated by Examples 1 and 3 after 1000h are obtained as follows: the residual stress of the 1# alloy developed in Example 1 is 294.65MPa, and the stress relaxation rate is 5.86%; the residual stress of the 3# alloy developed in Example 3 is 242.57MPa, and the stress relaxation rate is 18.2%. It can be seen that the strength and room temperature stress relaxation resistance of the developed 1# alloy are significantly higher than those of the 3# alloy, but the comprehensive performance of the 3# alloy is also very excellent, which is significantly higher than the performance that can be achieved by the Cu-Cr-Zr alloy developed by the current traditional process. In addition, the 1#-4# alloys regulated by Examples 1-4 are further evaluated for their high temperature stress relaxation resistance at 150℃. It can be seen from Table 4 that the high temperature stress relaxation resistance of the 1#-4# alloys is relatively excellent, and the relaxation rate of the 1# alloy is only 16.365% after 24h high temperature stress relaxation test. After detailed TEM and HRTEM structural characterization, such as Figure 5 , 6 As shown in Figure 7. As can be seen from the figure, a large number of nano-dispersed particles and dislocation lines are distributed in the final state matrix of the 1# alloy developed in Example 1, and the nano-dispersed particles, precipitate phase and dislocation form a good coupling distribution feature, that is, the nano-precipitate phase, the dispersed particles and the dislocation can be entangled with each other in the alloy matrix and evenly dispersed, and the size of the dislocation cell formed is relatively small. In addition, through high-resolution electron microscopy, it can be found that there are certain differences between the sizes of the formed precipitates, that is, nano-dispersed particles of various sizes and shapes are formed, and because the composition and process design and regulation are reasonable, the nano-dispersed particles in the matrix of the alloy are not seriously coarsened after the high-temperature stress relaxation test, which makes it not only maintain a good strengthening effect, but also pin the existing dislocations to annihilate each other during the relaxation process. It is the role of these aspects that makes the alloy have excellent high-temperature stress relaxation resistance.

[0110] On this basis, by further changing the hot working process of the developed series of alloys, especially the pre-aging control process, not only the process flow is significantly shortened, but also the comprehensive performance of the series of alloys is significantly changed. It can be seen from Table 3 that after being regulated by Examples 5-8, although the strength and conductivity of the developed series of alloys are lower than those of the alloys developed in Examples 1-4, they are still relatively excellent. The strength of the 1# alloy is close to 600MPa, and the conductivity is 60.3%IACS. The strength of the 2#, 3# and 4# alloys is also between 550 and 600MPa, but the conductivity is also as high as 82.8%IACS. It can be seen that the nano-precipitation and dislocation coupling distribution effects of the series of alloys after the short-process technology regulation of Examples 5-8 are slightly reduced, which is not as good as the coupling effect of the nanophase and dislocation in the series of alloys regulated by Examples 1-4, but the coupling effect is still good. The high-temperature stress relaxation resistance of the 1-4# alloys regulated by Examples 5-8 was further evaluated, as shown in Table 4, Figure 8 As shown. As can be seen from the figure and the table, the four typical alloys still show very excellent high temperature stress relaxation resistance, among which the high temperature stress relaxation resistance of alloy 1# is better than that of alloy 1# regulated in Example 1. However, in comparison, if the typical alloy 1# is regulated by comparative example 1, that is, after the solid solution treatment is introduced, the strength of the alloy is not only reduced (as shown in Table 3), but also the stress relaxation resistance of the alloy plate in the final state is poor, reaching 22.1%, which exceeds the expected value (20%) for practical application. In addition, in order to compare the effectiveness of the developed preparation process, the present application also compares the process route of first performing solid solution quenching treatment before aging, as shown in comparative example 1, and the corresponding performance test results are shown in Tables 3 and 4. As can be seen from the table, the alloy developed in comparative example 1 not only has low strength and conductivity, but also has poor corresponding stress relaxation resistance, which further highlights the superiority of the process developed in the present application, and once again proves that if the nano-dispersed particles, precipitated phases and dislocations cannot be well coupled and distributed, then the corresponding comprehensive performance is difficult to be significantly improved.

[0111] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0112] This application is to coordinate and coordinate the formation of nano-precipitate phase and its coupling distribution characteristics with dislocations by the integrated coordination of the Cr and Zr content and their matching ratios of Cu-Cr-Zr alloys, C and N microalloying, and subsequent composite physical field coordination and coordination of cast structure, two-stage high temperature heat treatment, hot rolling, ultra-low temperature cycle deep cold rolling deformation and pre-aging processes. Finally, based on the acquisition of multi-size nano-dispersed particles, precipitation phase and dislocation coupling distribution characteristics, the strength, conductivity and stress relaxation resistance of the developed series of alloys are significantly improved, which is significantly higher than the corresponding performance of traditional Cu-Cr-Zr alloys. The high-strength, high-conductivity, high-stress relaxation resistance modified copper alloy material and its preparation method developed by the present invention can well meet the urgent needs of high-strength, high-conductivity and high-stress relaxation resistance copper alloys for manufacturing typical components in many high-tech fields such as electronics industry, aerospace, instrumentation and household appliances. Therefore, this invention preparation method is not only very suitable for application in many high-tech fields, especially in the field with special requirements for high-strength and high-conductivity new copper alloys, but also especially for the problems that often occur in the application process of lead frame materials, such as poor stress relaxation resistance, etc., which can be well solved. It can be seen that the reasonable regulation of the distribution characteristics of nano-dispersed particles, precipitate phase and dislocation coupling is the key to significantly improving the strength, conductivity and stress relaxation resistance of the series of alloys.

[0113] In addition, this preparation technology also has certain guiding significance for the further development, processing and application of high-strength and high-conductivity copper alloys and other similar metal materials in other fields. It is worthy for copper alloy processing companies to pay attention to this invented alloy and its preparation process so that it can be promoted and applied as soon as possible.

[0114] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified copper alloy sheet, characterized in that: In terms of mass percentage, the modified copper alloy plate comprises: 0.8-1.5wt% of Cr element, 0.05-0.3wt% of Zr element, 0.001-0.10wt% of C element, 0.001-0.10wt% of N element, and the rest is Cu element.

2. The modified copper alloy sheet material according to claim 1, characterized in that: In terms of mass percentage, the modified copper alloy sheet material comprises: 0.8-1.4wt% of the Cr element, 0.05-0.22wt% of the Zr element, 0.001-0.10wt% of the C element, 0.001-0.10wt% of the N element, and the rest being the Cu element; and / or a weight ratio of the Cr element to the Zr element of 5-13:

1.

3. The modified copper alloy sheet material according to claim 1 or 2, characterized in that: The modified copper alloy plate includes nano dispersed particles, and the nano dispersed particles include nano carbide dispersed particles and nano nitride dispersed particles, wherein the mass content of the nano carbide dispersed particles is 0.005-0.5wt%, preferably 0.015-0.048wt%, and / or the mass content of the nano nitride dispersed particles is 0.0043-0.43wt%, preferably 0.013-0.042wt%; And / or the dislocation density of the modified copper alloy sheet is 1.1×10 15 ~2.0×10 15 m -2 , and / or the modified copper alloy plate further includes a precipitate phase, and the nano-dispersed particles and the precipitate phase are both dispersedly distributed.

4. The modified copper alloy sheet material according to any one of claims 1 to 3, characterized in that: The tensile strength of the modified copper alloy plate is 554.3-628.2 MPa, the yield strength of the modified copper alloy plate is 525.6-626.1 MPa, the conductivity of the modified copper alloy plate is 60.3-84.2% IACS, the room temperature and 1000h stress relaxation rate of the modified copper alloy plate is 5.86-18.2%, and the hardness of the modified copper alloy plate is 152.2-209.4 HV.

5. A method for preparing the modified copper alloy sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Step S1, preparing ingredients according to the contents of Cr, Zr and Cu in claim 1, and sequentially melting, heat-insulating, physically stirring and temperature-controlled casting the ingredients to obtain a copper alloy ingot; Step S2, sequentially performing a first high-temperature heat treatment, a first cooling treatment, a second high-temperature heat treatment, a second cooling treatment, hot rolling deformation, and a third cooling treatment on the copper alloy ingot to obtain a hot-rolled copper alloy plate; Step S3, sequentially subjecting the hot-rolled copper alloy sheet to a first ultra-low temperature cycle deep cold rolling deformation and a first aging treatment to obtain a first deformed copper alloy sheet; Step S4, subjecting the first deformed copper alloy sheet to a second ultra-low temperature cycle deep cold rolling deformation to obtain a modified copper alloy sheet; Wherein, the melting and the heat preservation are carried out in a graphite crucible in a vacuum medium frequency induction furnace, and the stirring and the casting are carried out in a nitrogen atmosphere; The starting rolling temperature of the hot rolling deformation is 700-840°C, and the final rolling temperature of the hot rolling deformation is >500°C.

6. The preparation method according to claim 5, characterized in that: The step S1 comprises: Step S11, when the vacuum degree is less than 0.1 Pa, subjecting the ingredients to a first heating and a first heat preservation in the graphite crucible, and then heating and melting and a second heat preservation to obtain a copper alloy melt; Step S12, subjecting the copper alloy melt to a first physical field stirring and a first cooling treatment in sequence, and then subjecting the copper alloy melt to a second physical field stirring and a second cooling treatment in sequence in a nitrogen atmosphere, and then subjecting the copper alloy melt to the temperature-controlled casting; Wherein, the pressure of the nitrogen atmosphere is 10 4 ~10 5 Pa; and / or, the temperature of the first insulation is 300-400° C., and the time of the first insulation is 30-50 min; and / or, the temperature of the second insulation is 1200-1300° C., and the time of the second insulation is 10-20 min; And / or, the first physical field stirring time is 30s to 90s, and the temperature of the copper alloy melt after the first cooling treatment is 1100 to 1200°C; And / or, the second physical field stirring time is 30s to 90s, and the temperature of the copper alloy melt after the second cooling treatment is 1150 to 1250°C.

7. The preparation method according to claim 5 or 6, characterized in that: In step S2, the temperature of the first high temperature heat treatment is 850-980°C, the heating rate of the first high temperature heat treatment is >100°C / min, and the time of the first high temperature heat treatment is 2-20h; And / or, the cooling rate of the first cooling treatment is >120°C / min; And / or, the temperature of the second high temperature heat treatment is 700-840°C, the heating rate of the second high temperature heat treatment is >100°C / min, and the time of the second high temperature heat treatment is 10-60min; And / or, the cooling rate of the second cooling treatment is >120°C / min; And / or, the deformation amount of the hot rolling deformation is 70-80%, and the deformation amount of each pass of the hot rolling deformation is 10-20%; And / or, the cooling rate of the third cooling treatment is >100°C / s.

8. The preparation method according to any one of claims 5 to 6, characterized in that: When the first aging temperature is 380-500° C. and the first aging time is 7-15 hours, the modified copper alloy sheet is obtained through the step S3 and the step S4; Wherein, the temperature of the first ultra-low temperature cycle deep cold rolling deformation is -100 to -190°C, the deformation amount of the first ultra-low temperature cycle deep cold rolling deformation is 50 to 65%, and preferably the number of cycles of the first ultra-low temperature cycle deep cold rolling deformation is >15 times; The heating rate of the first aging is >50°C / min; And / or, the temperature of the second ultra-low temperature cycle deep cold rolling deformation is -100 to -190°C, the deformation amount of the second ultra-low temperature cycle deep cold rolling deformation is 40 to 65%, and the number of cycles of the second ultra-low temperature cycle deep cold rolling deformation is >15 times.

9. The preparation method according to any one of claims 5 to 6, characterized in that: When the first aging temperature is 380-500° C. and the first aging time is 0.2-3 hours, the preparation method further comprises: Step S5, sequentially subjecting the copper alloy sheet obtained after the second ultra-low temperature cycle deep cold rolling deformation to a second aging treatment, a third ultra-low temperature cycle deep cold rolling deformation, a third aging treatment and a fourth ultra-low temperature cycle deep cold rolling deformation to obtain the modified copper alloy sheet.

10. The preparation method according to claim 9, characterized in that: In step S5, the temperature of the second aging is 380-480°C, the time of the second aging is 0.5-5h, and the heating rate of the second aging is >50°C / min; And / or, the temperature of the third ultra-low temperature cycle deep cold rolling deformation is -100 to -190°C, the deformation amount of the third ultra-low temperature cycle deep cold rolling deformation is 40 to 65%, and the number of cycles of the third ultra-low temperature cycle deep cold rolling deformation is >10 times; The temperature of the third aging is 350-460°C, the time of the third aging is 15-25h, and the heating rate of the third aging is >50°C / min; And / or, the temperature of the fourth ultra-low temperature cycle deep cold rolling deformation is -100 to -190°C, the deformation amount of the fourth ultra-low temperature cycle deep cold rolling deformation is 40 to 65%, and the number of cycles of the fourth ultra-low temperature cycle deep cold rolling deformation is >10 times.